2013
DOI: 10.1371/journal.pone.0062860
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Olfactory Ensheathing Cells from Different Sources for Spinal Cord Repair

Abstract: Spinal cord injury (SCI) induces a permanent disability in patients. To this day no curative treatment can be proposed to restore lost functions. Therefore, extensive experimental studies have been conducted to induce recovery after SCI. One of the most promising therapies is based on the use of olfactory ensheathing cells (OECs). OECs can be obtained from either the olfactory bulbs (OB-OECs) or from olfactory mucosa (OM-OECs), involving a less invasive approach for autotransplantation. However the vast majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…GBCs are positive for early neuronal differentiation markers such as Mash1, Neurogenin1, N-CAM, Sox2, and nestin (Gordon et al, 1995;Beites et al, 2005;Thakur et al, 2014), hence confirming that they are neural progenitor cells, while HBCs express keratin 5 and keratin 14 but are negative for neuronal markers (Carter et al, 2004) (see Table 1). However, only specific antibodies GBC-2 and GBC III were used to isolate GBCs from the OE by FACS, according to recent data (Chen et al, 2004;Krolewski et al, 2013;Thakur et al, 2013Thakur et al, , 2014, while ICAM-1 was Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/25/15 10:27 PM Human Gorrie et al, 2010;Kachramanoglou et al, 2013;Tabakow et al, 2013;Xie et al, 2013 Rat Rizek andKawaja, 2006;Kalincik et al, 2010;Centenaro et al, 2011;Kueh et al, 2011;Paviot et al, 2011;Stamegna et al, 2011;Tharion et al, 2011;Mayeur et al, 2013;Ishihara et al, 2014Dog Granger et al, 2012Ziege et Rat Kalincik et al, 2010;Centenaro et al, 2011;Paviot et al, 2011;Stamegna et al, 2011;Ishihara et al, 2014 S100 OECs Human Gorrie et al, 2010;Kachramanoglou et al, 2013;Tabakow et al, 2013Rat Centenaro et al, 2011 ( used to purify HBCs (Iwai et al, 2008;Fletcher et al, 2011;…”
Section: Gbcs and Hbcs: Characteristics And Potential Therapeutic Valmentioning
confidence: 99%
“…GBCs are positive for early neuronal differentiation markers such as Mash1, Neurogenin1, N-CAM, Sox2, and nestin (Gordon et al, 1995;Beites et al, 2005;Thakur et al, 2014), hence confirming that they are neural progenitor cells, while HBCs express keratin 5 and keratin 14 but are negative for neuronal markers (Carter et al, 2004) (see Table 1). However, only specific antibodies GBC-2 and GBC III were used to isolate GBCs from the OE by FACS, according to recent data (Chen et al, 2004;Krolewski et al, 2013;Thakur et al, 2013Thakur et al, , 2014, while ICAM-1 was Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/25/15 10:27 PM Human Gorrie et al, 2010;Kachramanoglou et al, 2013;Tabakow et al, 2013;Xie et al, 2013 Rat Rizek andKawaja, 2006;Kalincik et al, 2010;Centenaro et al, 2011;Kueh et al, 2011;Paviot et al, 2011;Stamegna et al, 2011;Tharion et al, 2011;Mayeur et al, 2013;Ishihara et al, 2014Dog Granger et al, 2012Ziege et Rat Kalincik et al, 2010;Centenaro et al, 2011;Paviot et al, 2011;Stamegna et al, 2011;Ishihara et al, 2014 S100 OECs Human Gorrie et al, 2010;Kachramanoglou et al, 2013;Tabakow et al, 2013Rat Centenaro et al, 2011 ( used to purify HBCs (Iwai et al, 2008;Fletcher et al, 2011;…”
Section: Gbcs and Hbcs: Characteristics And Potential Therapeutic Valmentioning
confidence: 99%
“…Several preclinical SCI studies have reported the occurrence of axonal extension, remyelination and neuroprotection after OEC transplantation (34,35,36,37,38). OECs migrate to injured sites and secrete a large number of factors that are necessary for the growth, development, differentiation, and maturation of different types of neurons and reduce astrocyte activity and glial scar formation (39,40). Spinal cord regeneration and functional recovery depend on the nature and source of OECs, the injury model, the graft cell preparation, the time of transplantation, and the transplantation procedures (25).…”
Section: Olfactory Ensheathing Cellsmentioning
confidence: 99%
“…OECs can be harvested from the olfactory bulb or from olfactory mucosa. The donor site morbidity is higher for the olfactory bulb source (bulb source is frequently used in animal models worldwide) and less invasive for olfactory mucosa, this approach being better and recommendable as cell source for autologous transplantation 31 . Iwatsuki transplanted the whole olfactory mucosa containing olfactory epithelium, lamina propria, and OECs and showed improvement in functional recovery after spinal cord injury 32 .…”
Section: Spinal Cord Injuriesmentioning
confidence: 99%